Improving land VSP resolution through the use of a broadband vibroseis source - Dean, Timothy; Tulett, J.; Puckett, M.; Lane, D. (2013)
© 2013 SEG.Seismic vibrators are the preferred sources for land vertical seismic profile (VSP) surveys as they are relatively repeatable, controllable, have high energy, have a low environmental impact, and are cost-effective. Unfortunately, due to the mechanical and hydraulic constraints of the vehicles, the typical swept bandwidth has been quite limited, typically of the order of 3 octaves. The bandwidth and quality of VSP data can be increased by using state-of-the art vibrator equipment but this has generally required the use of the latest buggy-mounted vibrators, compromising well-site logistics and transportation safety. The introduction of new, truckmounted vibrators has enabled the transmission of signals with a frequency bandwidth of 6.6 octaves compared to previous models which can only transmit 2.5 octaves. In this paper we show that dramatic improvements in seismic data quality can be achieved by extending the bandwidth used for Vibroseis VSPs. These increases are dependent, however, on the use of modern vibrators, specialised low-frequency enhancing sweeps, and downhole sensors with an extended frequency response range.